Sistem Pemantauan Kesuburan Tanaman Pohon Durian menggunakan Internet Of Things (IOT) - Anjellita Sundari Sumarsono; Novriyenni Novriyenni; Milli Alfhi Syari (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Durian is one of the leading fruit commodities with high economic value in various tropical regions, including Indonesia. However, the durian cultivation process often faces challenges related to unstable environmental conditions, such as temperature fluctuations, soil moisture, and nutritional deficiencies which can affect the level of plant fertility and the quality of the fruit produced. Therefore, an effective and efficient monitoring system is needed to optimize durian plant care. This research aims to develop a fertility monitoring system for durian trees using Internet of Things (IoT) technology which can help farmers manage the environmental conditions of plants in real-time. The designed system uses various sensors, such as soil moisture sensors, air temperature and humidity sensors, light intensity sensors, and soil nutrient sensors, to collect relevant environmental data. The data obtained from these sensors is then processed by a microcontroller and sent via the IoT network to a cloud-based storage platform. The trial results show that this system can monitor environmental conditions with high accuracy and provide appropriate maintenance recommendations, thereby increasing efficiency in managing durian plants.